Synergistic metabolism of carbon and nitrogen: Cyanate drives nitrogen cycle to conserve nitrogen in composting system. (October 2022) - Wen, Xiaoli; Sun, Ru; Cao, Ziyi; Huang, Yite; Li, Jixuan; Zhou, Yucheng; Fu, Mengxin; Ma, Liangcai; Zhu, Pengfei; Li, Qunliang
Graphical abstract: Highlights: HCO3 – was used as a cycling substrate for cyanate metabolism. Cyanate metabolism drove the nitrogen cycle to promote nitrogen deposition. The abundance of cynS, hao, and nifH in T was higher than that in CP. The abundance of narG, narH, nirK, norB, and nosZ decreased with composting. Abstract: In this study, HCO3 – was used as a co-substrate for cyanate metabolism to investigate its effect on nitrogen cycle in composting. The results showed that the carbamate content in experimental group (T) with HCO3 – added was higher than that in control group (CP) during cooling period. Actinobacteria and Proteobacteria were the dominant phyla for cyanate metabolism, and the process was mediated by cyanase gene ( cynS) . The cynS abundance was 16.6% higher in T than CP. In cooling period, the nitrification gene hao in T was 8.125% higher than CP. Denitrification genes narG, narH, nirK, norB, and nosZ were 25.64%, 35.33%, 45.93%, 36.62%, and 36.12% less than CP, respectively. The nitrogen fixation gene nifH in T was consistently higher than CP in the late composting period. Conclusively, cyanate metabolism drove the nitrogen cycle by promoting nitrification, nitrogen fixation, and inhibiting denitrification, which improved nitrogen retention and compost quality.